Mirada a la práctica religiosa en contextos virtuales durante el COVID-19 - Pérez Amores, Grecy (Ílu, 2024)
By exploring some of the transformations that occurred in the daily religious practices of different communities during the initial months of the COVID-19 pandemic, we examined the responses of these religious communities, which were mediated by ICTs. The research aimed to delve into the processes of adapting religious rituals and celebrations, focusing on virtualization and digitization. Additionally, it analyzed the role of mass media in shaping narratives about religious practices during the pandemic. Finally, we sought to understand how religious communities addressed conflicts and existential uncertainties during that period. Questions such as: What implications did the pandemic situation have for religious communities? To what extent can we speak of a redefinition of sacred spaces? How did technology help resolve cultic difficulties faced by religious congregations? And what was the mass media's portrayal of these religious practices? To answer these questions, we employed virtual ethnography of spaces mediated by ICTs and conducted interviews to collect offline religious experiences. The results revealed that the resilience demonstrated by individuals within these religious communities reflected their ability to reformulate and adapt religious practices using digital tools.